2012
DOI: 10.1007/s10554-012-0037-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of myocardial perfusion reserve at 1.5 and 3.0 Tesla: a comparison to fractional flow reserve

Abstract: The objective of this study was to compare quantitative analysis of cardiac magnetic resonance (CMR) perfusion at 1.5 and 3 T against fractional flow reserve (FFR) as measured invasively. FFR is considered by many investigators to be a reliable standard to determine hemodynamically significant coronary artery stenoses. Quantitative 1.5 and 3 T CMR is capable to noninvasively determine myocardial perfusion reserve, but have not been compared against each other and validated against FFR as standard reference. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…Studies such as Fractional Flow Reserve Versus Angiography for Multivessel Evaluation (FAME) and Clinical Outcomes Utilizing Revascularization and Aggressive Drug Evaluation (COURAGE) initiated a shift from PCI as the treatment of choice based on anatomic CAD to a more nuanced use of PCI guided by the hemodynamic significance of CAD and by recognizing that optimal medical therapy is equal or favorable in many patients with CAD. 18,19 Furthermore, FAME demonstrated that the routine measurement of FFR results in significantly reduced mortality and myocardial infarction rates at 2 years of follow-up in patients with multivessel CAD undergoing PCI with drug eluting stents. 18 Noninvasive assessment of hemodynamic CAD with stress MPI may further benefit patient outcome and costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies such as Fractional Flow Reserve Versus Angiography for Multivessel Evaluation (FAME) and Clinical Outcomes Utilizing Revascularization and Aggressive Drug Evaluation (COURAGE) initiated a shift from PCI as the treatment of choice based on anatomic CAD to a more nuanced use of PCI guided by the hemodynamic significance of CAD and by recognizing that optimal medical therapy is equal or favorable in many patients with CAD. 18,19 Furthermore, FAME demonstrated that the routine measurement of FFR results in significantly reduced mortality and myocardial infarction rates at 2 years of follow-up in patients with multivessel CAD undergoing PCI with drug eluting stents. 18 Noninvasive assessment of hemodynamic CAD with stress MPI may further benefit patient outcome and costs.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Furthermore, FAME demonstrated that the routine measurement of FFR results in significantly reduced mortality and myocardial infarction rates at 2 years of follow-up in patients with multivessel CAD undergoing PCI with drug eluting stents. 18 Noninvasive assessment of hemodynamic CAD with stress MPI may further benefit patient outcome and costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the reported PPV varies across these studies, the NPV is consistently high (Table 2). In a direct comparison, 3.0 T MPI-MR was found to be superior to 1.5 T MPI-MR for the detection of FFR-positive lesions [44]. In 1493 patients with known or suspected CAD, a negative dobutamine stress MR was associated with a <0.5 % 4-year event rate in patients with a low or intermediate pre-test probability of CAD [45].…”
Section: Comparison With Ffrmentioning
confidence: 93%
“…For example, in a recent metaanalysis of 12 studies reporting the diagnostic performance of CMR in stable CAD using FFR as the reference standard, on a coronary territory basis, pooled sensitivity was 88 % and pooled specificity was 89 %, suggesting high diagnostic accuracy of CMR for detection of flow-limiting stenosis [47]. Among the studies, however, the rate of actual FFR measurements in vessels included in analysis varied from 12 % to 100 %, with fewer than 75 % of vessels undergoing direct FFR interrogation in 10 of the studies [47][48][49]. This may lead to significant error, since it is well known that patients with< 50 % stenosis on ICA may have functionally significant stenosis (FFR≤0.80) [50], and that patients with stenosis severity>50 %, or even>70 %, often have FFR values>0.80 [2,3].…”
Section: Non-invasive Fractional Flow Reserve-limitationsmentioning
confidence: 99%